Working guide to pumps and pumping stations : calculations and simulations - Menon, E. Shashi (Gulf Professional Pub., 2010)
A plain language guide to the tools and techniques needed to ensure efficiency, Working Guide to Pump and Pumping Stations provides practicing engineer and senior field personnel with a quick but rigorous exposition of pumps, including applications. In this book, readers find expert advice for determining TDH, NPSH, BHP and driver power requirements, discharge temperature, parallel/series operation and their impact on the operating conditions; developing system-head curves and performance considerations; pump selection for multi-product operations. The book also emphasizes the understanding.